2003
DOI: 10.1029/2003gl018896
|View full text |Cite
|
Sign up to set email alerts
|

Etna 2002 eruption imaged from continuous tilt and GPS data

Abstract: On the night of October 26, 2002, intense explosive activity and lava effusion began suddenly on the southern flank of Mt. Etna at an altitude of 2750 m. During the 27 and 28 October, a long field of eruptive fractures propagated radially along the north‐eastern flank of the volcano. Ground deformation changes recorded between 26 and 27 October from GPS and tilt data collected at the permanent geodetic network of Mt. Etna, were modeled to infer the positions and dimensions of the two dikes. The observed deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
101
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(110 citation statements)
references
References 10 publications
9
101
0
Order By: Relevance
“…The GPS data showed that at the 2002 eruption onset the eastern flank had undergone a marked eastward acceleration and then it continued to move eastward in the two following years with more than double the velocity of the previous years (see displacement vectors in Figure 4) and with a near constant rate (see continuous data in Figure 2). Therefore the 2002 eruption, characterized by two intrusions along the South and Northeast rifts (Figure 1), provoked the start of the current phase of the marked acceleration of the eastward sliding and, in particular, the main contribution was furnished by the 2002 NE dike which induced the bigger displacements on the volcano edifice and sped up movement along the Pernicana fault [Aloisi et al, 2003[Aloisi et al, , 2006. The NE dike intruded radially with a depth not greater than 2.1 ± 0.4 km [Aloisi et al, 2006] from the surface.…”
Section: Discussion and Conclusive Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…The GPS data showed that at the 2002 eruption onset the eastern flank had undergone a marked eastward acceleration and then it continued to move eastward in the two following years with more than double the velocity of the previous years (see displacement vectors in Figure 4) and with a near constant rate (see continuous data in Figure 2). Therefore the 2002 eruption, characterized by two intrusions along the South and Northeast rifts (Figure 1), provoked the start of the current phase of the marked acceleration of the eastward sliding and, in particular, the main contribution was furnished by the 2002 NE dike which induced the bigger displacements on the volcano edifice and sped up movement along the Pernicana fault [Aloisi et al, 2003[Aloisi et al, , 2006. The NE dike intruded radially with a depth not greater than 2.1 ± 0.4 km [Aloisi et al, 2006] from the surface.…”
Section: Discussion and Conclusive Remarksmentioning
confidence: 99%
“…Nine stations collect data at 1 Hz sampling rate 24 h/d, the remaining stations collect data for 8 hour sessions per day [Patanè et al, 2005]. [Aloisi et al, 2003;Patanè et al, 2005].…”
Section: The 2003-2004 Datamentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Volcano monitoring during the eruption resulted in a large amount of high-quality data on ground deformation [Aloisi et al, 2003], gravity [Branca et al, 2003], volcanology, petrology [Andronico et al, 2004] and structural geology [Neri et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…In geomatics, a consolidated approach for integrated surface displacement monitoring of unstable slopes is the creation of a network of benchmarks surveyed by Global Navigation Satellite System (GNSS) and by Automated Total Stations (ATS) [Aloisi et al, 2003;Gunzburger et al, 2005;Puglisi et al, 2005;Mattia et al, 2007;Bertacchini et al, 2009]. A more innovative remote sensing approach is the use of Ground Based InSAR (GB-InSAR) [Tarchi et al, 2003;Pieraccini et al, 2006].…”
Section: Introductionmentioning
confidence: 99%